ANALISIS VEGF PADA PERGERAKAN GIGI ORTODONTI SETELAH PEMBERIAN SEDUHAN KOPI ROBUSTA ( COFFEACANEPHORA) - Herniyati Herniyati (Jurnal Teknosains, 2016)
Background: Orthodontic tooth movement depends on bone remodeling. VEGF plays an important role in bone remodeling in both pressure area and tension area. Robusta coffee contains caffeine, chlorogenic acid and caffeic acid. Caffeine may increase osteoclastogenesis, and caffeic acid has antioxidant effects that may reduce oxidative stress in osteoblasts Objective: To analysis of VEGF of orthodontic tooth movement post robusta coffeesteeping administration. Material and methods: The experimental laboratories research used 16rats  were divided into 2 groups. Group A: the rats were applied with  orthodontic mechanical force (OMF) and group B: OMF + coffee steeping of 20mg /100 g of BW. OMF was conducted by applying  ligature wire with a diameter of 0.20 mm on the molar-1 (M-1) and both incivus of right maxilla. Subsequently, M-1 of right maxilla was moved to mesial  with Niti closed coil spring. Observations were made on days 15 and 22 by taking the gingival crevicular fluid by putting paper point on the gingival sulcus of mesio-and disto-palatal area of M-1 of right maxilla to determine the levels of VEGF using ELISA method. Results: the administration of Robusta coffee steeping increased the levels of VEGF in both compression area and tension area (p <0.05).The levels of VEGF in tension area larger than the compression area(p >0.05).Conclusion: the Robusta coffee steeping administration increased the levels of VEGF oforthodontic tooth movement ,therefore it may improve alveolar bone remodeling process and it may be an alternative to accelerate orthodontic treatment.